Corrective Feedback in Speaking Class - Dewi, Desi Surlitasari (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2015)
The objectives of the research are to: (1)find out types of corrective feedback used by the lecturers in Speaking activity at the second semester of English Department Students of Universitas Riau Kepulauan Batam in the academic years of 2013/2014; and (2) find out student’s response towards the lecturer’s feedback.The research was carried out at Universitas Riau Kepulauan Batam, from March 2014 to May 2014.The subject of the research is the second semester of English Department Unrika. The researcher did observation to take the data of corrective feedback used in class and used closed questionnaire, observation, and interview to find out student’s response towards the lecturer’s feedback.Then, the data was analyzed by using triangulation. Based on the result of data analysis, it was found that the lecturer used five types of corrective feedback. Recast was the feedbackmostly used by lecturer. It was followed by repetition, metalinguistic feedback, elicitation, and explicit correction. The student’s response toward feedback given by the lecturer were mostly negative. Most of the students were not comfortable with themselves when given feedback by the lecturers. However, some of them found it was okay because it was for their own good.  Key Words: Corrective Feedback; Speaking Skill; and  Student’s Response